2020
DOI: 10.1002/er.6342
|View full text |Cite
|
Sign up to set email alerts
|

Be, Li and Sc functionalized borane B 6 H 6 and carborane C 2 B 4 H 6 for hydrogen storage: A comparison using first principles approach and molecular dynamics simulations

Abstract: Hydrogen adsorption properties of functionalized closo-dicarborane (C 2 B 4 H 6) and boranes (B 6 H 6) are studied and compared using quantum chemical methods. More number of H 2 molecules gets adsorbed on metal functionalized carboranes than metal functionalized boranes considered in this work. One, three and five H 2 molecules get adsorbed on each metal atom in B 6 H 4 Be 2 , B 6 H 4 Li 2 and B 6 H 4 Sc 2 complexes, respectively. One additional H 2 molecule per metal atom gets adsorbed on C 2 B 4 H 4 Be 2 , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The parameters are set to a constant number of atoms, a constant volume, and constant temperatures of 300 and 400 K. We set the MD simulation time to 1.5 ps to have enough time to complete the calculation, which is consistent with the published reports. 56 , 63 , 68 70 Figure 9 a,b shows the molecular dynamics simulation results of the adsorption of 24 H 2 molecules by 6Sc-COF-1 at 300 and 400 K, respectively. It can be seen that the COF-1 structure does not undergo significant deformation and the six Sc atoms are still stably adsorbed on the COF-1 layer without aggregation at both 300 and 400 K. One of the four hydrogen molecules adsorbed by each Sc atom escapes at 300 K, and all of the adsorbed H 2 molecules are released when the temperature is 400 K. It is demonstrated that the adsorption and desorption of hydrogen molecules can be achieved within a narrow temperature range of 300–400 K and 6Sc-COF-1 has excellent reversibility as a hydrogen storage material.…”
Section: Resultsmentioning
confidence: 99%
“…The parameters are set to a constant number of atoms, a constant volume, and constant temperatures of 300 and 400 K. We set the MD simulation time to 1.5 ps to have enough time to complete the calculation, which is consistent with the published reports. 56 , 63 , 68 70 Figure 9 a,b shows the molecular dynamics simulation results of the adsorption of 24 H 2 molecules by 6Sc-COF-1 at 300 and 400 K, respectively. It can be seen that the COF-1 structure does not undergo significant deformation and the six Sc atoms are still stably adsorbed on the COF-1 layer without aggregation at both 300 and 400 K. One of the four hydrogen molecules adsorbed by each Sc atom escapes at 300 K, and all of the adsorbed H 2 molecules are released when the temperature is 400 K. It is demonstrated that the adsorption and desorption of hydrogen molecules can be achieved within a narrow temperature range of 300–400 K and 6Sc-COF-1 has excellent reversibility as a hydrogen storage material.…”
Section: Resultsmentioning
confidence: 99%